Perancangan Aplikasi Pemesanan Jasa Kebersihan Menggunakan Algoritma Apriori Pada PT. Woshi Woshi Berbasis Android - Gulo, Meliyus; Nurhayati, Nurhayati (Universitas Methodist Indonesia, 2025)
PT. Woshi Woshi is a growing cleaning services company. Several issues frequently arise, including the manual ordering of cleaning services, often done offline or directly with the admin. The company lacks a system capable of analyzing customer ordering patterns, resulting in multiple product orders being placed simultaneously. To address these issues, this study developed an Android-based cleaning service ordering application using the Apriori Algorithm. The algorithm was implemented to simplify Android-based cleaning service ordering and generate more efficient cleaning service order reporting. The resulting cleaning service ordering system is capable of analyzing cleaning service ordering patterns using the Android-based Apriori Algorithm. The resulting ordering patterns are intended to recommend products to customers, provide discount strategies, and demonstrate the company's ability to manage transaction data using the Apriori Algorithm for easier and more accurate calculations.